Etyka urzędników czy etyka administracji publicznej? Uwagi na tle książki Tomasza Barankiewicza „W poszukiwaniu modelu standardów etycznych administracji publicznej w Polsce” - Skuczyński, Paweł (Filozofia Publiczna i Edukacja Demokratyczna, 2014)
The article reviews a book of Tomasz Barankiewicz „W poszukiwaniu modelu standardów etycznych administracji publicznej w Polsce” published by Wydawnictwo Katolickiego Uniwersytetu Lubelskiego in 2013. The book concerns some important problems in the field of ethics of public administration and the article recommends it to anyone who has interest in professional ethics and public management. The article emphasises the role of ethics in public administration and the pursuit of building a model of public administration ethics. It summarises the content of the book and discusses some theoretical problems connected to the models proposed by author of the book. In particular the relation between moral responsibility and reflexive institutions is being discussed and the dependence of theory of public administration and some political theories as well.